Konsep landasan filosofis pengembangan ilmu bersumber pada nilai-nilai ke-UGM-an - Heri Santoso; Koento Wibisono Siswomihardjo,; Arqom Kuswanjono (Universitas Gadjah Mada, 2016)
This research is motivated by crisis, especially of UGM (Universitas Gadjah Mada) identity andof philosophical foundations of its scientific development. This study aims to inventory, analyzesynthesize, critically evaluate, as well as construct a philosophical foundation of scientific development originating in UGM values. The study employs a reflective, systematic philosophical research model.Data consists mainly of documents data, supported by field data collected through participantobservation and in-depth interviews. Material objects of research are values contained in the university’slegal basis or statute, symbols of its identity attributes, and thoughts of its leaders, while formal objectof research is philosophy, particularly philosophy of values (axiology) and philosophy of science. Datawill be analyzed using elements of methodical study of philosophy, especially interpretive analysis in aheuristic framework to come to conclusion.The results show that: First, history of ideas indicates that GMU scholars have proposed andjustified concept and model of scientific development based on GMU (Gadjah Mada University)values, that is the concept of “Pancasila as (1) guidance (2) orientation and (3) paradigm of scientificand technological development.” Scientific models that were successfully developed are (1) Pancasilaicscience and knowledge and Science of State and Law of Pancasila (Ilmu Negara dan Hukum Pancasila)by Notonagoro; (2) Pancasila Economics (Ilmu Ekonomi Pancasila) by Mubyarto; and (3) PropheticSocial Science (Ilmu Sosial Profetis) by Kuntowijoyo. Second, the concept of scientific developmentdeveloped by GMU-based scholars is actually built on basic assumptions that science is not value-freeand, thereby, teleological, i.e. acting for the sake of human civilization, usefulness, and happiness. These axiological and metaphysical assumptions are heavily influenced by a metaphysical belief that recognizes the existence and power of God. These axiological and metaphysical assumptions epistemologically imply that there is a source of knowledge and truth other than scientific knowledge and truth.